An assessment of the nutritional status of underfive children in a rural area of Thrissur district, Kerala, India - R., Priyanka; Vincent, Vivin; M. P., Jini; Saju, C. R. (International Journal Of Community Medicine And Public Health, 2016)
Background: India contributes to more than one-third of the under-nourished children in the world. According to NFHS 3 survey, 43% under-five children in India were under-weight, and 48% were stunted. In Kerala, the prevalence of underweight among under-five children was 28.8%, and stunting 21.1%. The objectives of the present study were to assess the nutritional status of under-five children and to find the factors associated with under-nutrition. Methods: A community based cross sectional study was conducted among 360 under-five children. Socio-demographic, dietary and clinical details of the children were collected using pre-tested semi-structured questionnaire. Weight and height of children were measured using standard protocols. Children were considered as having under-weight and stunting if their weight for age and height for age Z scores were below -2 SD of WHO standards. Results: Out of 360 children, 48.9% were males and 51.1% were females. The prevalence of under-weight and stunting was 28.3% and 14% respectively. The prevalence of underweight and stunting was found to be higher among females. Risk factors like low birth weight, inadequate protein intake, respiratory infections and diarrheal disease in the past year, and presence of worm infestation were significantly associated with under-nutrition. Full immunization was found to be protective against under-nutrition. Conclusions: The risk factors for under-nutrition start from the womb itself. This, together with inadequate dietary consumption and frequent infections plays a significant role in the occurrence of under-nutrition among under-five children.